PEMENUHAN HAK KONSUMEN TERKAIT JAMINAN PEMBERIAN GANTI RUGI OLEH PENYELENGGARA POS - Muhamad Sofyan Fahrezi (2023)
Developments in the trade sector and the Covid-19 phenomenon have caused people to shop for necessities online, namely by using a marketplace, one of which is shoppe, so that goods delivery services are needed by Postal Operators. Practically there are still many obstacles, one of which is the loss of consumer goods. In this study the authors want to analyze some of the problems regarding conflicting rules regarding the provision of compensation guarantees by postal operators and the resulting consequences. The method used by the author is Normative Juridical, with the aim of analyzing the certainty of postal administrator responsibility if there is a conflict of rules regarding guarantees for compensation by postal organizers in Government Regulation of the Republic of Indonesia Number 15 of 2013 concerning Implementation of Law Number 38 of 2009 concerning Post with Law no. 8 of 1999 concerning Consumer Protection and the consequences of implementing this article regarding the fulfillment of consumer rights. The author discusses the certainty of rules in fulfilling the right to guarantee compensation in practice using the rules of the Government Regulation of the Republic of Indonesia Number 15 of 2013 concerning the Implementation of Law Number 38 of 2009 concerning Post, but in terms of the legal principles of applicability which have a higher strength, namely the Law No. 8 of 1999 concerning Consumer Protection. The two consequences arising from the application of Article 10 paragraph 2 (i) of the Government Regulation of the Republic of Indonesia Number 15 of 2013 concerning the Implementation of Law Number 38 of 2009 concerning Post are more detrimental to consumers and consumers who have to accept the risk if such losses occur if the losses are greater if not insured. Suggestions from the author that legal certainty is needed to ensure that consumer rights can be fulfilled and in applying the rules, legal protection is needed.